1996
DOI: 10.1046/j.1526-4610.1996.3609547.x
|View full text |Cite
|
Sign up to set email alerts
|

Divalproex Sodium in Headache: Literature Review and Clinical Guidelines

Abstract: Divalproex sodium is an anticonvulsant agent approved for use either alone or in combination with other antiepileptic drugs for simple and complex absences seizures and mania. Four double-blind placebo-controlled studies have confirmed that divalproex sodium/valproate is an effective migraine treatment. In all of the clinical studies, whether open, retrospective, or placebo-controlled and double-blind, valproate was an effective preventive treatment for migraine. There was a reduction in the number of migraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 30 publications
2
45
1
Order By: Relevance
“…GABA agonist mechanisms have been implicated in both the prophylactic and acute treatment of migraine. Valproate, a well established migraine prophylactic medicine (Silberstein, 1996), enhances GABAergic neurotransmission by activation of the GABA synthetic enzyme, glutamic acid decarboxylase (Loscher, 1981), and by inhibition of the GABA degradative enzymes, GABA aminotransferase (Loscher, 1981;Maitre et al, 1978) and succinate semialdehyde dehydrogenase (van der Laan et al, 1979). Although valproate does not block mechanically induced cortical spreading depression in the cat (Kaube & Goadsby, 1994), it has been proposed that an increase in inhibitory GABAergic neurotransmission may suppress the pathophysiological events that underlie migraine aura (Cutrer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…GABA agonist mechanisms have been implicated in both the prophylactic and acute treatment of migraine. Valproate, a well established migraine prophylactic medicine (Silberstein, 1996), enhances GABAergic neurotransmission by activation of the GABA synthetic enzyme, glutamic acid decarboxylase (Loscher, 1981), and by inhibition of the GABA degradative enzymes, GABA aminotransferase (Loscher, 1981;Maitre et al, 1978) and succinate semialdehyde dehydrogenase (van der Laan et al, 1979). Although valproate does not block mechanically induced cortical spreading depression in the cat (Kaube & Goadsby, 1994), it has been proposed that an increase in inhibitory GABAergic neurotransmission may suppress the pathophysiological events that underlie migraine aura (Cutrer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent AEs are nausea, alopecia, tremor, asthenia, dyspepsia, somnolence and weight gain [51]. Hepatotoxicity and pancreatitis are the most serious AEs but irreversible hepatic dysfunction is extremely rare in adults [52]. Divalproex carries a high risk of congenital abnormality [46].…”
Section: Valproic Acidmentioning
confidence: 99%
“…The enhancement of GABA activity is thought to be the mechanism in preventing migraine attack [5]. Several clinical studies have demonstrated the efficacy of sodium valproate as prophylactic agent in migraine [9,10]. The drug was therefore recently included in the Italian [11] and American guidelines [12] on diagnosis and treatment of migraine, at dosages of 800-1500 mg/day.…”
Section: Discussionmentioning
confidence: 99%